1973
DOI: 10.1088/0031-8949/7/3/007
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Periodic Variations in Geomagnetic Activity and Their Solar Cycle Dependence

Abstract: A search for periodic oariations in geomagnetic actiuity and their solar cycle dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Our spectral analysis shows that the multi‐day oscillations tend to occur during the latter part of the declining solar cycle and the corresponding correlation between the density periodicities and those of solar wind and geomagnetic activity index is high, which is consistent with previous studies of the long‐term variations of solar wind and geomagnetic activity data [e.g., Hauska et al , 1973; Nayar et al , 2001]. Hauska et al [1973] performed a power spectrum analysis on the geomagnetic activity Kp data for several solar cycles (1932–1969), and showed a clear solar cycle dependence of periodic variations at periods of 27, 13, 9 and 6 days. Using solar wind data and geomagnetic activity index Ap during 1965–1999, Nayar et al [2001] demonstrated that the periodicities in the range of 5 to 50 days have their peak amplitude during the declining phase of the solar cycle.…”
Section: Resultssupporting
confidence: 91%
“…Our spectral analysis shows that the multi‐day oscillations tend to occur during the latter part of the declining solar cycle and the corresponding correlation between the density periodicities and those of solar wind and geomagnetic activity index is high, which is consistent with previous studies of the long‐term variations of solar wind and geomagnetic activity data [e.g., Hauska et al , 1973; Nayar et al , 2001]. Hauska et al [1973] performed a power spectrum analysis on the geomagnetic activity Kp data for several solar cycles (1932–1969), and showed a clear solar cycle dependence of periodic variations at periods of 27, 13, 9 and 6 days. Using solar wind data and geomagnetic activity index Ap during 1965–1999, Nayar et al [2001] demonstrated that the periodicities in the range of 5 to 50 days have their peak amplitude during the declining phase of the solar cycle.…”
Section: Resultssupporting
confidence: 91%
“…This value is certainly due to the frequency resolution of the spectra. We therefore think that an average value with a period of 27.0 days, as found in [7], is most correct. However, we also feei, that the error in the rotation period or the dipole, given in [14], is a very low estimate.…”
Section: 2mentioning
confidence: 80%
“…This raises the assumption that the sector boundary, which probably originates at the westward boundary of the active longitude, also exists during the total life-time of the active longitude. We suggest that, on the average, stable interplanetary Physica Scripta 7 sector boundaries develop somewhere, between the westward boundary, and the center of the active longitude, and that these boundaries are normally connected with the change of polarity from fields directed towards the sun to fields directed away from the sun. This implies that even when a well developed four sector structure does not exist in the interplanetary medium, a two sector structure will be observed.…”
Section: 2mentioning
confidence: 90%
See 1 more Smart Citation
“…[40] Several studies note these rotation periods in solar wind data and in A p over many solar cycles [Hauska et al, 1973;Prabhakaran Nayar et al, 2001;Temmer et al, 2007]. In particular, Prabhakaran Nayar et al [2001] looks at variations of solar wind and A p at periodicities of 9 and 27 days and finds that both track the solar cycle; that is the peak power for both occur near solar maximum.…”
Section: Results From Individual Years 321 Year 2002mentioning
confidence: 99%